The 1st International Conference on Energy, Power and Environment 2021
DOI: 10.3390/engproc2021012036
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Climatic Impacts of Photovoltaic Systems Operating High-Efficiency Irrigation Systems: A Case Study of the Government Subsidy Scheme for Climate-Smart Agriculture in Punjab, Pakistan

Abstract: This paper presents the results of a field study conducted in the Punjab, Pakistan, to evaluate the socio-economic and climatic impact of Photovoltaic (PV) systems installed under government subsidy scheme for operating high efficiency irrigation systems (HEIS) i.e., drip and sprinkler irrigation systems. Agriculture provides livelihood to almost half of the rural population and recent energy crisis in the country has adversely affected the rural communities. Farmer’s dependence on fossil fuels has significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…For example, in the month of June, total water requirement is 3234.816 cubic meter and the PV system fulfills this demand. PV Systems fulfill the required crop water require ment, similar to results found in the research study conducted by Raza et al [35] and Ta moor et al [56]. If we compare Figures 6 and 7, we see that the PV system fulfills the required cro requirement by only using 28% of potential water supply, and 72% of the potential wate supply has not been used.…”
Section: Solar-drip Simulation Tool (Sosit) Output Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…For example, in the month of June, total water requirement is 3234.816 cubic meter and the PV system fulfills this demand. PV Systems fulfill the required crop water require ment, similar to results found in the research study conducted by Raza et al [35] and Ta moor et al [56]. If we compare Figures 6 and 7, we see that the PV system fulfills the required cro requirement by only using 28% of potential water supply, and 72% of the potential wate supply has not been used.…”
Section: Solar-drip Simulation Tool (Sosit) Output Resultssupporting
confidence: 85%
“…For example, in the month of June, total water requirement is 3234.816 cubic meters and the PV system fulfills this demand. PV Systems fulfill the required crop water requirement, similar to results found in the research study conducted by Raza et al [35] and Tamoor et al [56]. Figure 7 shows the actual water demand and supply by the designed PV system.…”
Section: Solar-drip Simulation Tool (Sosit) Output Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Photovoltaic power is also more cost-effective than a conventional diesel irrigation system, which provides farmers in remote areas with cheaper access to water and improves their socio-economic and living conditions [24,25]. Research works [26,27] have investigated the socio-economic and environmental effects of using photovoltaic-operated high-efficiency irrigation systems on drip irrigation owners. The results showed that photovoltaic-powered high-efficiency irrigation systems have a major effect on resource savings, such as energy savings, labor cost savings, and water usage reduction, as well as improving crop yields and farmer benefits, all of which help to improve the quality of life in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Electricity from utility grid or diesel generators are typically used to pump water in agricultural sector. However, further development of these systems is hinder by increasing fossil fuel prices, carbon dioxide emissions, and unreliable utility grid and infrastructure in rural and arid areas [ 11 ]. In the agricultural sector, Pakistan seems to have more than 600,000 water tube wells.…”
Section: Introductionmentioning
confidence: 99%